2022
DOI: 10.1186/s12876-022-02390-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of folic acid supplementation to halt and even reverse the progression of gastric precancerous conditions: a meta-analysis

Abstract: Background Current data indicate that supplements such as folic acid and vitamin B may be beneficial in halting and even reversing atrophic gastritis, intestinal metaplasia and intraepithelial neoplasia, generally referred to as gastric precancerous conditions(GPC). However, there is no Meta-analysis article to evaluate the prevention and treatment of folic acid in the gastric precancerous conditions. We therefore conducted a meta-analysis to confirm the efficacy of folic acid in treating GPC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…A meta-analysis of randomized controlled trials had concluded a beneficial effect of FA on gastric precancerous lesions. 27 However, FA could not relieve the symptoms caused by CAG and is mainly recommended for patients with low folate levels. 28 The findings in the current trial confirmed that Moluodan could improve the global condition of gastric mucosa and halt the progression of advanced lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of randomized controlled trials had concluded a beneficial effect of FA on gastric precancerous lesions. 27 However, FA could not relieve the symptoms caused by CAG and is mainly recommended for patients with low folate levels. 28 The findings in the current trial confirmed that Moluodan could improve the global condition of gastric mucosa and halt the progression of advanced lesions.…”
Section: Discussionmentioning
confidence: 99%
“…FA has been considered a potential chemopreventive agent for GC in both animal studies and clinical intervention trials, 25,26 providing evidence for its value in clinical use. A meta‐analysis of randomized controlled trials had concluded a beneficial effect of FA on gastric precancerous lesions 27 . However, FA could not relieve the symptoms caused by CAG and is mainly recommended for patients with low folate levels 28 .…”
Section: Discussionmentioning
confidence: 99%
“…These observations were confirmed by recent meta-analysis of the role of FA supplementation in reversal of gastric precancerous conditions. 93 Daily doses of 20–30 mg of FA in the duration of 3–6 months were associated with significant reversal of both, atrophic gastritis and intestinal metaplasia (RR: 1.77, 95% CI: 1.32–2.37). 93 …”
Section: Reversibility Of Intestinal Metaplasiamentioning
confidence: 96%
“… 93 Daily doses of 20–30 mg of FA in the duration of 3–6 months were associated with significant reversal of both, atrophic gastritis and intestinal metaplasia (RR: 1.77, 95% CI: 1.32–2.37). 93 …”
Section: Reversibility Of Intestinal Metaplasiamentioning
confidence: 96%
“…In contrast, the risk of death from GC was found to be lowered in a trial including the use of low-dose dietary vitamins (physiological rather than pharmaceutical dosages) ( 133 ). A recent study on the reversal of GPL with folic acid supplementation found that folic acid can help heal atrophic gastric mucosal lesions and reverse intestinal metaplasia in GPL patients ( 134 ).…”
Section: Treatmentmentioning
confidence: 99%